Earnest Hemingway: Sketches Of Life And Works - El Tayeb El Mikashfi, Lubab (Gezira Journal of Educational Sciences and Humanities, 2021)
The purpose of this paper is to bring to light the essence of Hemingway's literary achievements for the benefit of the audience; who are concerned with English literature in general and American literature in particular. Investigating Hemingway's life and works reveals his invaluable contribution to English literature in USA and the world-over. His variety of themes related to the period between the two world wars and the simple journalistic style he adopted speak for his mastery of the art of modern narration